Network Epistemology. - HUMPHREYS, PAUL (Episteme (Edinburgh University Press), 2009)
A comparison is made between some epistemological issues arising in computer networks and standard features of social epistemology. A definition of knowledge for computational devices is provided and the topics of nonconceptual content and testimony are discussed.